ZOMBIE DAN DIVERSIFIKASI DALAM MASA KRISIS KEUANGAN GLOBAL - Novita, Santi; Tjahjadi, Bambang; Irwanto, Andry (Universitas Muhammadiyah Malang)
This study aims to examine whether a firm with a higher degree of related diversification is less likely to have a zombie condition during the global financial crisis. The research sample is non-financial firms listed on the Indonesia Stock Exchange in the year of the global financial crisis from 2007-2009. Data are analyzed using logistic regression. The results of the study indicate that a firm with a higher degree of related diversification is less likely to have a zombie condition during the global financial crisis. Furthermore, the effect of this diversification proves to be higher for a firm with a domestic orientation than an international orientation